혼합형 유전알고리즘을 이용한 조선소 스키드 순서 최적화 - 최민재(Min-Jae Choi); 권영근(Yung-Keun Kwon) (한국컴퓨터정보학회논문지, 2023)
본 연구는 조선소 소조립 공정에서 스키드 투입 순서 최적화를 통해 전체 작업시간을 단축시키는 새로운 유전 알고리즘 방법을 제안한다. 하나의 해는 스키드 번호들의 순열로 표현되며 그러한 표현에 적합한 유전 연산자들을 적용하였다. 또한 탐색 성능의 개선을 위해 UniDev라 불리우는 기존의 휴리스틱 알고리즘을 적절하게 변형하여 유전 알고리즘과 결합하였다. 특히 UniDev에서 느린 스키드 탐색 부분을 그리디 알고리즘의 형태로 변경하였다. 매우 큰 규모의 문제에 대해시뮬레이션을 수행한 결과 Multi-Start 탐색과 UniDev기반 혼합형 유전알고리즘에 비해 본 연구에서 제안하는 방법이 안정적으로 작업시간을 최소화함을 관찰하였다. In this paper, we propose a novel genetic algorithm to reduce the overall span time by optimizing the skid insertion sequence in the shipyard subassembly process. We represented a solution by a permutation of a set of skid ids and applied genetic operators suitable for such a representation. In addition, we combined the genetic algorithm and the existing heuristic algorithm called UniDev which is properly modified to improve the search performance. In particular, the slow skid search part in UniDev was changed to a greedy algorithm. Through extensive large-scaled simulations, it was observed that the span time of our method was stably minimized compared to Multi-Start search and a genetic algorithm combined with UniDev. KCI Citation Count: 0